Zeta Converter as a Voltage Stabilizer with Fuzzy Logic Controller Method in The Pico Hydro Power Plant - Eviningsih, Rachma Prilian; Nugraha, Anggara Trisna; Fatqurrochman, Muhammad Ilham (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
The development of the use of environmentally friendly renewable energy has been widely carried out, one of which is the use of energy as a turbine driver at the Pico Hydro Power Plant. The main problem in the use of energy, especially water energy is the flow of water which can affect the flow of water used to rotate the turbine so that the voltage on the DC link cannot be kept constant. Therefore, in this paper, we design and simulate the process of charging lead acid batteries with a zeta converter and a Pico Hydro Power Plant as the main source. The use of batteries in this system as energy storage if the river flow is heavy, the charging process will be carried out and if the river flow decreases, the battery will help to supply household loads. Due to the river flow which is very dependent on natural conditions, the power generated is also fluctuating so we need a control that can produce a constant output voltage from the zeta converter which is used for the battery charging process. Therefore, the aim of using a Fuzzy Logic Controller (FLC) is to keep the output voltage of the zeta converter constant so that it can maintain battery life. The results obtained in the close loop simulation test are a constant output voltage of 14.4 V and an output current of 6.64 A so that it can be used for the battery charging process that will be used for household lighting.